Analysis of the Use of Various Languages in Msme Digital Marketing on Instagram: Case Study of Pukis Kota Baru - Butarbutar, Della Agaveni; Hasugian, Anastasia Boru; Sitanggang, Cindy B; Dalimunthe, Afifah Nida Suhailah Br; Ginting, Gevy Ketia; Badawi, Agil; Dalimunthe, Syairal Fahmy (CV. Rayyan Dwi Bharata, 2024)
The rapid development of technology requires MSME Entrepreneurs to be more creative and innovative. Instagram is one of the Social Media that is widely used in promoting their products today. Like the @pukiskotabaru account which uses Instagram as a digital marketing tool. The purpose of this study is to determine the type of use of language varieties in video content on the @pukiskotabaru Instagram account and assess the effectiveness of the use of language varieties by the @pukiskotabaru Instagram account in attracting attention and influencing consumers. In this study, researchers used qualitative methods with data collection techniques then used content analysis techniques, where researchers collected several video content to find several interesting posts or videos in the process of digital marketing of their products. The results of this study indicate that the use of language varieties in the video content of the @pukiskotabaru Instagram account consists of spoken language varieties, written language varieties, and nonstandard language varieties, the use of persuasive written language varieties and strong visuals to attract consumer interest and the use of these language varieties has proven to be quite effective in attracting attention and influencing consumers.